The association between nutritional status and physical activity among auxiliary police in UiTM Selangor, Malaysia / Harunal Aminnur Sharif Jaafar - Jaafar, Harunal Aminnur Sharif (2016)
The nutritional status and physical activity level of Auxiliary Police may have an interacflon with one another. This’ study aims (i) to assess nutritional status (via BMI) of the Auxiliary Police of UiTM in Selangor, (ii) to determine physical activity level of the Auxiliary Police and (iii) to identify association between nutritional status and physical activity level of Auxiliary Police. 122 Auxiliary Police (108 male and 14 female) aged betweeq 18 and 65 years old from five selected campuses located at Kampus Puncak Alam, Puncak Perdana, Shah Alam, Sungai Buloh and Selayang, Selangor have involved in this cross sectional study. The instrument used is International Physical Activity Questionnaire (IPAQ) to assess the physical activity of Auxiliary Police. Auxiliary Police from five different campuses are chosen using simple random sampling. The data of this study were analwed by using Statistical Package for the Social Sciences (SPSS) sofiware. The BMI mean score of of Auxiliary Police is 27.17 i 4.46. Mean score for physical activity level is 1796.28 14115.28. There is a significant correlation between BMI with physical activity level (p< 0.01) and physical activity level with sitting time (p=0.045).